CULTURAL-BASED TOURISM IN CIREBON: A STUDY OF COMMODIFICATION IN CULTURAL TOURISM - Nyai Kartika; Reiza Dienaputra; Susi Machdalena; Awaludin Nugraha (Universitas Padjadjaran, 2022)
The people of Cirebon have various religious, ethnic and cultural backgrounds. However, they can live harmoniously in such diversity. Cirebon is interesting to explore due to its abundant culture-based tourism. However, in the tourism industry, the process of commodification is inevitable as part of current development. Therefore, this study employed a qualitative method using historical, social, and cultural commodification approaches expected to provide a better overview and information regarding culture-based tourism in Cirebon. The commodification of culture allows cultural forms to be a tradable commodity. It changes culture as originally a social relationship into culture as an economic relationship. Thus, it is important to apply historical and social approaches in the study to determine the existence of cultural heritage. This encourages the researchers to further discover the extent to which commodification is implemented in the culture-based tourism industry in Cirebon, aiming to provide information to the public to give more attention as well as participate in preserving cultural heritage in the midst of the challenges of modern times. The results of this study show an overview of cultural tourism in Cirebon, in which various elements of society are expected to help preserve and maintain culture as self-identity.